Bromination of 2, 7′-bi-indolyls and quinazolin-7-ones. Issue 47 (25th November 2015) - Mielczarek, Marcin; Bhadbhade, Mohan; Chen, Rui; Kumar, Naresh; Black, David StC.
Abstract: Efficient regioselective procedures for bromination of 2, 7′-bi-indolyls and quinazolin-7-ones using molecular bromine and N -bromosuccinimide were developed to afford a wide range of novel mono-, di-, tri- and tetrabrominated derivatives with various substitution patterns. Protection of the nitrogen atoms in the 2, 7′-bi-indolyl scaffold by acetyl, benzenesulfonyl and carbonyl groups was investigated. Stability of 2, 7′-bi-indolyls in the presence of strong bases was explored to discover formation of imines followed by the unusual ring opening reaction. Single crystal X-ray crystallography and NMR spectroscopy were employed in order to assign structural isomers of dibrominated quinazolin-7-ones. A new method for the synthesis of macrocyclic tetra-indolyls via acid-catalyzed coupling of monobromo-2, 7′-bi-indolyls is reported and a possible mechanism of the reaction presented. Graphical abstract: